Timing and Positioning of Simulated Hail Damage Effects on Wheat Yield in Kansas: 2015–2016 and 2016–2017 Growing Seasons - R. P. Lollato; A. de Oliveira Silva; R. E. Maeoka; G. P. Bavia; L. Bonassi; B. R. Jaenisch (Kansas Agricultural Experiment Station Research Reports, 2018)
Hail events often decrease wheat yields in Kansas; however, estimates of yield loss due to hail event timing and position relative to the flag leaf are only available for older varieties. Our objectives were to quantify wheat yield losses as affected by timing of hail event relative to the crop development and positioning of the damage relative to the flag leaf. A total of 14 hail damage treatments including seven different timings during the growing season (boot, anthesis, watery ripe, milk, soft dough, hard dough, and ripe) and two different positioning relative to the flag leaf (above or below) were evaluated in a trial conducted in Manhattan, KS, during the 2015–2016 and 2016–2017 growing seasons. Hail damage was simulated by bending 100% of the stems within each plot, which averaged approximately 15 bu/a both growing seasons across treatments, ranging from non-significant to 20.4 bu/a. The lowest grain yield (or highest grain yield loss) due to simulated hail occurred when treatments were imposed during milk stage or anthesis (above and below flag leaf) and during soft dough stage below flag leaf in 2015–2016. Delaying treatment to hard dough, when most of the photosynthates have already been translocated to the grain, also decreased grain yields when compared to the control both years, especially when stem bending occurred below the flag leaf. More years of research are needed to achieve robust estimates of wheat yield loss due to hail damage, but these preliminary data indicate that wheat grain yield is more sensitive to hail damage during the interval between anthesis and the milk stage of grain development.
Keywords: wheat hail damage; Kansas wheat; Agronomy field research